STAKE’S EVALUATION MODEL: METODE PENELITIAN - Eliyah, Eliyah; Aslan, Aslan (Prosiding Seminar Nasional Indonesia, 2025)
This research aims to provide an overview of the STAKE program evaluation model. The method used is a literature review method with a qualitative-descriptive approach. The research results show that: 1. The stake evaluation model, also known as the consideration evaluation model. This evaluation model has two matrices, namely a description matrix and a judgment matrix. Each matrix has two research stages. The description matrix consists of two stages, namely the intense stage (goals/hopes) and observation (the reality of the goal). Meanwhile, the judgment matrix also has two stages, namely standard and consideration. Each matrix and stage each has three components, namely, antecedents (initial conditions), transactions (implementation/application) and outcomes (results). Commonly used data collection techniques and tools are interviews, observation and documentation. The data analysis technique commonly used is descriptive-qualitative analysis technique with descriptive statistics. 2. An example of implementing a stake model program evaluation is the evaluation carried out by Science Study Program students at FTIK IAIN Bengkulu. The program evaluation they carried out was on the Biology learning program at SMA No. 10 Bengkulu City. "Between planning and implementation and science learning outcomes, learning planning with sufficient categories causes teachers to carry out learning not in accordance with process standards so that student learning outcomes do not meet the KKM." 3. The research plan created is an evaluation research design for the stake model program at FTIK IAIS Sambas. The object evaluated is the student's thesis which uses quantitative methods. Because it is still in draft form, accurate results have not yet been obtained, even though there is already a picture based on the results of the initial survey.